Mango flower induction in the brazilian northeast Semi-arid with gibberellin synthesis inhibitors - Do, M. A.; Mouco, C.; Ono, E. O. [UNESP]; Rodrigues, J. D. [UNESP] (My University, 2010)
Mangoes in the Brazilian semi-arid stands out in the national scenario due to high yields and fruit quality, and also to the possibility of all-year production taking advantage of the climatic conditions as well as management technique (irrigation, pruning and growth regulators application) for plant growth and blossom control. Paclobutrazol soil drench applied is normally used for production management of mangoes. This research deals with the evaluation of the effect of foliar applied growth regulators to mango, cultivar 'Kent', as regard to their efficiency for blossom management, in order to allow off season mango production. Three growth regulators (prohexadione-Ca, trinexapac-ethyl and chlormequat chloride) were foliar applied, at two dosages and compared to paclobutrazol applied as soil-drench. In order to compare the effects of the treatment, data were recorded related to panicle emission (percentage and length), period of time until blossom and production, yield (number and plant weight) and post-harvest quality of the fruit (total soluble solids, titratable acidity, pH, firmness, flesh and skin color and appearance). The results showed that prohexadione-Ca and chlormequat chloride induced a 15-day early harvest, while paclobutrazol, alone or combined with prohexadione-Ca, allow to harvest 25 days in advance, when compared to trinexapac-ethyl and control trees. Growth regulators foliar applied and paclobutrazol applied as soil-drench delayed mangoes fruit ripening in post-harvest.
Keywords: Chlormequat chloride; Fruit quality; Production; Prohexadione-Ca; Trinexapac-ethyl